Bibliometric analysis of scientific papers on extracellular vesicles in kidney disease published between 1999 and 2022 - Hun, Marady; Wen, Huai; Han, Phanna; Vun, Tharith; Zhao, Mingyi; He, Qingnan (Frontiers in Cell and Developmental Biology, 2023)
Recently, there has been an increasing interest in extracellular vesicles (EVs) for use as potential therapeutic agents or natural drug delivery systems in kidney-related diseases. However, a detailed and targeted report on the recent condition of EVs research in kidney-related diseases is lacking. Therefore, this prospective study was designed to investigate the use of bibliometric analysis in a comprehensive overview of the current state of research and frontier trends in the field of EVs research in kidney-related diseases using visualization tools. The WoSCC was searched to identify publications related to EV research in kidney-related diseases since 1999. The Citespace, VOS Viewer software, the R Bibliometrix Package, and one online platform were used to analyze related research trends and stratify publication data and collaborations. From 1 January 1999 to 26 June 2022, a total of EVs 1122 articles and reviews were included. The number of articles regarding EVs in kidney-related diseases speedily rose yearly. It was reported that 6,486 authors from 1,432 institutions in 63 countries or regions have investigated the role of EVs in kidney-related diseases. The dozens of publications were from China and the United States, of which China conserved the dominant position in this field; meanwhile, Southeast University was the most active institution in all fields. Liu Bi-cheng, published the most papers on EVs, while Clotilde Théry had the most co-citations. The International Journal of Molecular Sciences published the most papers, while Kidney International was the most co-cited journal for EVs. We found that keywords from exosome related including exosome, extracellular vesicle, microvesicle, liquid biopsy; disease-related and pathological process-related include biomarker, microRNA, apoptosis, mechanism, systemic-lupus-erythematosus, acute kidney injury, chronic kidney disease. And AKI, CKD, SLE, exosome, liquid biopsy, and extracellular vesicle were the hotspot in EVs and kidney-related diseases research. The field of this field is in a fast upgrowth stage and its domain is likely to expand in the next decade. This research disseminates an all-around analysis of EVs in kidney-related diseases research, which may supply beneficial consults for investigators in this domain, and set new diagnostic, therapeutic, and prognostic ideas or methods in kidney-related diseases.